İhracatta örgütlenme modelleri ve Türkiye uygulaması sektörel dış ticaret şirketleri ile dış ticaret sermaye şirketlerinin vergilendirilmesi - Erdem, Serpil (My University, 2003)
Türkiye ekonomisi, 1970 'li yılların sonlarına gelindiğinde, sürekli olarak artan ithalat, giderek durgunlaşan ihracat , yükselişi önlenemeyen enflasyon, iç ve dış borç yükü, tablosu ile karşı karşıya kalmış ve cari işlemler dengesi ; 1977 yılında GSMH'nın % 8'ine, döviz gelirlerinin yüzde 92' sine ulaşmıştır. İşte tüm bunların sonucu 24 Ocak 1980 tarihinde açıklanan; Ekonomik İstikrar lkenin ihtiyaç duyduğu döviz girdisinin sağlanabilmesi için ihracatı teşvik sisteminde köklü değişiklikler yapılarak, Japonya, Güney Kore, Tayland, Brezilya ve hatta ABD' de ihracat örgütlemesi yapan ve büyük başarılar elde eden Genel Ticaret Şirketleri, modeli örnek alınarak şuandaki DTSŞ'nin oluşumuna izin verilmiştir. Ancak tarihsel süreç içerisinde, DTSŞ'lerinin büyük holding yada güçlü şirketlerin birer ihracat departmanı gibi çalıştıkları KOBİ'lerin ihracatına pek fazla bir katkı yapmadıkları gözlendiğinden, alternatif bir çözüm yolu olarak, İtalya'daki KOBİ'leri ihracata yönelten, Federexport ve bünyesindeki konsorsiyumlar örnek alınarak Çok Ortaklı Dış Ticaret Şirketleri modeli (bugünün Sektörel Dış Ticaret Şirketleri) uygulamaya konmuştur. Ülkemizde faaliyet gösteren üretici kesimin % 98'i KOBİ niteliğindeki şirketlerdir. KOBİ'lerin ihracata yöneltilmesi; ekonomik gelişmemizin sağlanabilmesi, istihdam sorununun çözümü, ülke refah düzeyinin yükseltilmesi için nerdeyse tek çözüm yoludur. Bu düşünceyle çalışmamıza ülkemizde ihracat örgütlemesi yapmak üzere kuruluşuna devletçe izin verilen SDŞ ve DTSŞ'ler konu edilerek, çalışmanın içeriğinde öncelikle örnek alınan dünya modellerinin hukuki yapılanmaları, fonksiyonları ve bu şirketlere devletlerce verilen teşvikler irdelenerek daha sonra Türkiye'de statü verilecek şirketlerin sahip olması istenen özellikler, hukuki yapılarının oluşumuna olanak sağlayan yasal düzenlemeler, fonksiyonları, fonksiyonların icrasını teşvik edecek devlet desteklemeleri ve bu şirketlerin vergi kanunları açısından değerlendirilmesi yapılarak izah edilmeye çalışılmıştır. Ancak yapılan tüm çalışmalar sonrası, bu şirketlerin hukuki yapılanmalarına olanak tanıyan mevzuaat hükümlerinin neredeyse tüm ticaret şirketlerini kapsayan genel hükümlerden ibaret olduğu, teşvik adı altında tanınan ayrıcalıkların ise yine hukuki alt yapı eksikliği nedeniyle uygulanamadığı ve bu nedenle de kendilerinden beklenen mikro ve makro yararları sağlayamadıkları ve süratle yeniden yapılanmalarının gerekli olduğu sonucuna varılarak alternatif çözüm yolları üretilmiştir. By the end of 1970 years, Turkish economy encountered with a tableau of internal and external debt burden , unpreventable inflation, continuous increasing import and export geting steady stil. The current account balance of the country reached up to 8 percent of Gross National Product in 1977 year and up to 92 percent of exchange revenues. So , as a result of above-mentioned facts as of 24 January 1980 Economic Stability Programme was declared. By this economic stability programme, in order to provide the needed currency, some radical changes in incentive system was concluded, aiming at increasing the export. While establishing the new incentive measures, General Trade Companies which had been succeessful in making export organizations of Japan , South Korea , Thailand , Brazil and even of the U.S.A. have been taken as a model. This model is currently called as Dış Ticaret Sermaye Şirketleri-Foreing Trade Incorporations But, in historical process , being observed that Foreing Trade Incorporations, have been activate as External Department of bigger Holdings or powerful Companies, and have not been influential in the export of Small and Medium sized Enterprises, as an alternative solution, Federexport and Consortiums in Federexport body have been taken as new model. Federexport and Corsortioums in Federexport body were very influential in assisting in the export of Small and Medium Enterprises in İtaly. By taking these instutitions as model, Multy Partnership External Trade Companies' (currently called as Sektörel Dış Ticaret Sermaye Şirketleri - Sectoral Foreing Trade Companies ) model have been put into Action. 98 percent of producers operating in our Country are companies in characteristic of small and medium sized enterprises. In order to conclude economic development , solve the employment problem , rise the country's welfare situation, directing the Small and Medium Sized Enterprises towards exportation is almost the only one solution. For this reason , in our study Sectoral Foreing Trade Companies and Foreing Trade Capital Companies, which their establishment are permitted by the State in order to organize export in our Country , has been taken as the matter. Legal structures of world models have been taken as an example , their functions and the incentives given by the states to these Companies have been researched firstly in content of the study. And than , the companies to be given status in Turkey which have different kind of special features , wiht legal regulations providing possibility to the establishment of their legal structures , their functions and state supports which will provide incentive for the performing of their functions , and the tax laws of these companies have been evaluated and explained in this study. However , after these studies , determined that the laws decree providing possibility to the establishment of legal structures of these companies were almostly consisting of general sentences including whole Trade Companies , and that favors called as incentives could not been performed because the lack of legal infrastructure , and for this reason these companies could not provide micro and macro benefits which are expected from themselves and a conclusion have been reached that these Companies should be reorganized quickly and alternative solutions methods have been developed.
Keywords: Dış ticaret; Dış Ticaret_Vergiler; İhracat (Dışsatım); Ticaret